617 Tisotumab vedotin shows immunomodulatory activity through induction of immunogenic cell death. (9th November 2020) - Gray, Elizabeth; Hensley, Kelly; Allred, Sean; Trueblood, Esther; Gosink, John; Thurman, Robert; Smith, Kaleb; Jacquemont, Celine; Bieda, Mark; Gow, Jason; Harris, Jeffrey; Brady, Lauren; et al.
Abstract : Background: Tisotumab vedotin (TV) is an investigational antibody-drug conjugate composed of a tissue factor (TF)-directed human monoclonal antibody covalently linked to the microtubule-disrupting agent monomethyl auristatin E (MMAE) via a protease-cleavable linker. TV demonstrated single agent activity (24% objective response rate [ORR]) in previously treated recurrent or metastatic cervical cancer (NCT03438396 ) where currently, there is no standard of care and ORRs are typically less than 15% and often of limited duration. 1–8 TV is currently being evaluated in combination with pembrolizumab (PD-1 inhibitor), bevacizumab, or carboplatin in cervical cancer (NCT03786081 ), or as a monotherapy in multiple other solid tumors (NCT03913741, NCT03485209, NCT03657043 ). The anti-tumor activity of TV may be multimodal as TV can induce tumor cell death through several mechanisms, including direct and bystander MMAE-mediated cytotoxicity, as well as antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), and immunogenic cell death (ICD)]. 9 10 To better characterize immune-mediated tumor cell killing by TV and further the rationale for combination with pembrolizumab, we set out to refine our understanding of TV-mediated ICD and subsequent immunomodulatory effects. Methods: We evaluated the ability of TV to mediate activation of immune cells in vitro using co-cultures of TF-expressing tumor cells and human peripheral blood mononuclear cells (PBMCs). We also assessed the ability of TV to induce recruitment of innate immune cells to tumors in vivo using a TF-expressing xenograft tumor model. Results: In vitro, tumor cells treated with TV showed several hallmarks of immunogenic cell death, including markers of endoplasmic reticulum (ER) stress and release of ATP and high mobility group protein B1 (HMGB1). Co-culture of TV-killed tumor cells with allogeneic human PBMCs led to innate immune cell activation (measured by upregulation of the costimulatory molecule CD86) and T cell proliferation. Combination with PD-1 blockade further amplified the immune response, leading to enhanced T cell proliferation and cytokine production. Moreover, in vivo studies demonstrated that TV treatment led to recruitment of F4/80+ and CD11c+ innate immune cells to xenograft tumors. Conclusions: These data show that, in preclinical models, TV induces immunogenic tumor cell death, which can promote activation and recruitment of immune cells to the tumor. The totality of in vitro and in vivo data provides evidence for the immunomodulatory effects of TV and bolsters rationale for combining TV with immune checkpoint agents. Ongoing analyses aim at further characterizing the immune response induced by TV in preclinical models and patients. Acknowledgements: We would like to thank Kristen Gahnberg for embedding and sectioning tissues for these studies and Anthony Cao for his early work identifying hallmarks of ICD in response to TV treatment in vitro. 9 Ethics Approval: Animals studies were approved by and conducted in accordance with Seattle Genetics Institutional Care and Use Committee protocol #SGE-029. Consent: N/A References: Van den berg YW, Osanto S, Reitsma PH, Versteeg HH. The relationship between tissue factor and cancer progression: insights from bench and bedside. Blood 2012;119(4):924–932. Miller DS, Blessing JA, Bodurka DC, Bonebrake AJ, Schorge JO. Evaluation of pemetrexed (Alimta, LY231514) as second line chemotherapy in persistent or recurrent carcinoma of the cervix: a phase II study of the Gynecologic Oncology Group. Gynecol Oncol 2008;110(1):65–70. Bookman MA, Blessing JA, Hanjani P, Herzog TJ, Andersen WA. Topotecan in squamous cell carcinoma of the cervix: A Phase II study of the gynecologic oncology group. Gynecol Oncol 2000;77(3):446–449. Garcia AA, Blessing JA, Vaccarello L, Roman LD. Phase II clinical trial of docetaxel in refractory squamous cell carcinoma of the cervix: a Gynecologic Oncology Group Study. Am J Clin Oncol 2007;30(4):428–431. Monk BJ, Sill MW, Burger RA, Gray HJ, Buekers TE, Roman LD. Phase II trial of bevacizumab in the treatment of persistent or recurrent squamous cell carcinoma of the cervix: a gynecologic oncology group study. J Clin Oncol 2009;27(7):1069–1074. Santin AD, Sill MW, Mcmeekin DS, et al. Phase II trial of cetuximab in the treatment of persistent or recurrent squamous or non-squamous cell carcinoma of the cervix: a gynecologic oncology group study. Gynecol Oncol 2011;122(3):495–500. Schilder RJ, Blessing J, Cohn DE. Evaluation of gemcitabine in previously treated patients with non-squamous cell carcinoma of the cervix: a phase II study of the Gynecologic Oncology Group. Gynecol Oncol 2005;96(1):103–107. Chung HC, Ros W, Delord JP, et al. Efficacy and safety of pembrolizumab in previously treated advanced cervical cancer: results from the phase II KEYNOTE-158 study. J Clin Oncol 2019;37(17):1470–1478. Alley SC, Harris JR, Cao A, et al . Tisotumab vedotin induces antitumor activity through MMAE-Mediated, Fc-Mediated, and Fab-Mediated Effector Functions In Vitro [abstract]. Cancer Res. 2019;79(13 Suppl):Abstract 221. Breij E, de Goeij B, Verploegen S, et al . An antibody-drug conjugate that targets tissue factor exhibits potent therapeutic activity against a broad range of solid tumors. Cancer Res 2014 ;74(4):1214–1226.